Strong Environmental Filtering Based on Hydraulic Traits Occurring in the Lower Water Availability of Temperate Forest Communities - Zhao, Jiale; Zhang, Yuhan; Xu, Jinshi; Chai, Yongfu; Liu, Peiliang; Cao, Ying; Li, Cunxia; Yin, Qiulong; Zhu, Jiangang; Yue, Ming (Frontiers in Plant Science, 2022)
The trait-based approaches have made progress in understanding the driving factors that underlie the community assembly process. However, the assembly process of plants communities in different environmental conditions based on hydraulic traits has not been studied in detail. Here, we aimed to explore the key traits that may shape community assembly patterns of the same community type but within different water availability. Natural Quercus wutaishanica forests were chosen as a suitable study system to test the difference between economic and hydraulic traits across water availability on the Loess Plateau(LP, semi-arid region) and Qinling Mountains(QL, humid region) of China, to understand their assembly processes. 75 plots were established separately in two sites, and 12 functional traits (7 hydraulic traits and 5 economic traits) of 167 species were focused. Community-weighted mean traits values and functional diversity indices were compared between the two sites. Canonical component analysis was performed to infer whether the changes of community traits and their relationships are driven by intraspecific variation or species turnover. Evidence for likely community assembly processes was tested using the null model to determine whether functional structure among 7 hydraulic traits and 5 economic traits was dominated by different ecological processes between two sites. We found that Q.wutaishanica forests in the Loess Plateau and Qinling Mountains showed entirely different hydraulic and economic traits. Moreover, hydraulic and economic traits coupled at the community level,which was primarily driven by species turnover. Hydraulic traits rather than economic traits (except for SD) showed more significant clustering patterns in QL than that on LP. Our results suggest a strong environment filtering process occurred hydraulic-based community assembly in the forest with low water availability, emphasize the critical role of multi-dimensional traits selecting like hydraulic traits in community assembly study, reveal the relationship of hydraulic and economic traits at the community level in temperate regions. These results have significant consequences for predicting plant species’ response to changes in the hydraulic traits due to drought climate change.